German foreign policy and Serbia during the mandate of Olaf Scholz's government - Mirosavljević, Igor (Political Life, 2025)
Paper explores German foreign policy regarding Serbia during the mandate of the government of Chancellor Olaf Scholz, who succeeded Angela Merkel in that position. Paper examines continuities and changes in the foreign policy towards Serbia, and determines key issues in relations from Berlin’s perspective in the period 2021-2024. From a theoretical point of view, paper is based on Charles Hermann's conceptualization of foreign policy changes. In addition to the prevailing continuities, related to priorities of regional stability, economic engagement, but also framework of initiatives for regional cooperation and process of European integration, adjustment changes and attempts of program changes are also identified in Germany's approach to Serbia. Key open issues on which German government took a more critical stance and (or) exerted more intense pressure were discussed: (1) (non)joining the regime of sanctions against Russian Federation, (2) deadlock in the process of normalization of relations between Serbia and Kosovo, (3) democratic backsliding in Serbia. Consequences are reflected in the deteriorating level of political relations between Germany and Serbia during most of the Olaf Scholz’s mandate.
Keywords: Germany, Serbia, Olaf Scholz’s government, foreign policy, foreign policy changes